The state of China-European Union economic relations - Uri Dadush; Marta Domínguez-Jiménez; Tianlang Gao (Bruegel, 2019)
China and the European Union have an extensive and growing economic relationship. The relationship is problematic because of the distortions caused by China's state capitalist system and the diversity of interests within the EU's incomplete federation. More can be done to capture the untapped trade and investment opportunities that exist between the parties. China's size and dynamism, and its recent shift from an export-led to a domestic-demand-led growth model, mean that these opportunities are likely to grow with time. As the Chinese economy matures, provided appropriate policy steps are taken, it is likely to become a less disruptive force in world markets than during its extraordinary breakout period.
Keywords: 330